2023
DOI: 10.1007/s11468-023-01810-3
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Nitride Plasmonic Nanohole Arrays for CMOS-Compatible Integrated Refractive Index Sensing: Influence of Layer Thickness on Optical Properties

Abstract: The combination of nanohole arrays with photodetectors can be a strategy for the large-scale fabrication of miniaturized and cost-effective refractive index sensors on the Si platform. However, complementary metal–oxide–semiconductor (CMOS) fabrication processes place restrictions in particular on the material that can be used for the fabrication of the structures. Here, we focus on using the CMOS compatible transition metal nitride Titanium Nitride (TiN) for the fabrication of nanohole arrays (NHAs). We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…3 and 4 , surface agents can change this phase difference, and the real part of relative permittivity becomes positive. This can be directly resulted from the fact that the effective permittivity of the decorated particle is no longer like an ideal metal, and the particle has moved away from its metallic properties [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…3 and 4 , surface agents can change this phase difference, and the real part of relative permittivity becomes positive. This can be directly resulted from the fact that the effective permittivity of the decorated particle is no longer like an ideal metal, and the particle has moved away from its metallic properties [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…They demonstrated that increasing TiN layer thickness enhances sensitivity, leading to potential advancements in on-chip plasmonic refractive index sensors. 305 TiN's low-index surfaces enable the growth of ultra-smooth, thin crystalline films essential for high-performance plasmonic and metamaterial devices, including hyperbolic metamaterials (HMMs). G. Naik et al constructed an epitaxial superlattice as a Hyperbolic metamaterial (HMM) using TiN, this study overcame fabrication limitations, achieving ultrasmooth layers of 5 nm thickness with sharp interfaces critical for superior HMM performance.…”
Section: Review Materials Advancesmentioning
confidence: 99%
“…The values of the complex refractive index were extracted using the software jreftran_rt.m, version 2.1 (Photonics Group ETH Zürich, Zürich, Switzerland) to fit the raw data [47]. For this fit, the optical properties of the TiN layer were taken from previous measurements of the sputtered material [34,48].…”
Section: Materials and Instrumentationmentioning
confidence: 99%
“…Being motivated by the possible application of the PAA/PAH bilayers as surface functionalization for optical biosensors using TiN-based plasmonic structures [34,48], we also performed measurements of the complex refractive index of the material in the wavelength range of 400 nm ≤ λ ≤ 1700 nm (Figure 7). The thickness of the polymer layer extracted from the fit is 10 nm.…”
Section: Layer-by-layer Deposition Of Polyelectrolytesmentioning
confidence: 99%